Simple synthesis of hierarchically structured partially graphitized carbon by emulsion/block-copolymer co-template method for high power supercapacitors - Mun, Yeongdong; Jo, Changshin; Hyeon, Taeghwan; Lee, Jaehyuk; Ha, Kyoung-Su; Jun, Ki-Won; Lee, Sang-Hyup; Hong, Seok-Won; Lee, Hyung Ik; Yoon, Songhun; Lee, Jinwoo (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
Hierarchical structure with macropores interconnecting mesopores of carbon material can remarkably improve the rate performance of electric double layer capacitor. However, preformed hard templates such as silica particles or polymer beads have been used in most synthetic procedures for them, resulting in an increase of manufacturing cost and time. Herein, we report novel method for synthesizing hierarchically structured macro/mesoporous partially graphitized carbon (MMPGC) for high power supercapacitor electrode material without pre-formed hard template. Instead of hard template, emulsion/block co-polymer co-template was used for generating macropores and mesopores, respectively. As a supercapacitor electrode material, MMPGC showed higher capacity retention at high current than ordered mesoporous carbon, which is characterized by cyclic voltammetry, galvanostatic charge discharge. In addition, the effect of macropores and partially graphitized wall on reducing resistance of supercapacitor electrode was analyzed in detail with electrochemical impedance spectroscopy fitting method. (C) 2013 Elsevier Ltd. All rights reserved.